Nitrogen-Containing Molecules: Natural and Synthetic Products Including Coordination Compounds - Matiadis, Dimitrios; Halevas, Eleftherios (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
A total of 16 original research articles. Contributions from 10 countries from 3 continents. Organic synthesis towards novel heterocyclic compounds. Fully characterized inorganic and organic molecules including X-ray crystallographic analysis. Cyclization reactions, reactivity of aromatic compounds and improved synthetic methodologies of important intermediate compounds.